2022
DOI: 10.1155/2022/9900146
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Low-Level Laser Therapy on Osseous Defects Distal to Mandibular Second Molar after Extraction of Impacted Third Molar

Abstract: Objective. To evaluate the efficiency of low-level laser therapy on the distal osseous defects of the mandibular second molar (M2) after the adjacent impacted third molar (M3) extraction. Methods. A total of 59 clinic cases were screened out, whose M3 were impacted and the distal alveolar bone of M2 had been destroyed horizontally. They were randomly divided into 2 groups based on whether they would have laser irradiation or not after M3 extraction. Then, postoperative complications of the 2 groups were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Low‐intensity laser can not only stimulate the proliferation and differentiation of osteoblasts but also increase the Alkaline phosphatase activity of osteoblasts 48 . Recent studies have found that low‐intensity lasers can also upregulate the expression of intracellular osteocalcin, thereby playing a role in promoting bone formation 19,49 . Studies have also found that low‐intensity laser can reduce the content of various types of inflammatory cells in gingival connective tissue and stimulate the activity of fibroblasts to accelerate gingival healing 50 …”
Section: Discussionmentioning
confidence: 99%
“…Low‐intensity laser can not only stimulate the proliferation and differentiation of osteoblasts but also increase the Alkaline phosphatase activity of osteoblasts 48 . Recent studies have found that low‐intensity lasers can also upregulate the expression of intracellular osteocalcin, thereby playing a role in promoting bone formation 19,49 . Studies have also found that low‐intensity laser can reduce the content of various types of inflammatory cells in gingival connective tissue and stimulate the activity of fibroblasts to accelerate gingival healing 50 …”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%